2020
DOI: 10.1136/bmjspcare-2020-002578
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver experiences with advanced cancer care: a qualitative study informing the development of an early palliative care pathway

Abstract: BackgroundPalliative care is an approach that improves the quality of life of patients and families facing challenges associated with life-threatening illness. In order to effectively deliver palliative care, patient and caregiver priorities need to be incorporated in advanced cancer care.AimThis study identified experiences of patients living with advanced colorectal cancer and their caregivers to inform the development of an early palliative care pathway.DesignQualitative patient-oriented study.Settings/part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…The CALM group reported greater perceived benefit on all CEQ items except discussion of cancer and treatment concerns. Most group differences reached significance at 6 months and presumably reflect the different emphases of CALM and usual care: whereas CALM is focused on psychological adaptation and response to the challenges of advanced disease, routine advanced cancer clinic visits focus on cancer-related symptoms and treatment 35 36. The unique factor-structure and internal-consistency patterns of the discussion of cancer and treatment concerns item relative to other CEQ items further indirectly reflect these different intervention targets.…”
Section: Discussionmentioning
confidence: 99%
“…The CALM group reported greater perceived benefit on all CEQ items except discussion of cancer and treatment concerns. Most group differences reached significance at 6 months and presumably reflect the different emphases of CALM and usual care: whereas CALM is focused on psychological adaptation and response to the challenges of advanced disease, routine advanced cancer clinic visits focus on cancer-related symptoms and treatment 35 36. The unique factor-structure and internal-consistency patterns of the discussion of cancer and treatment concerns item relative to other CEQ items further indirectly reflect these different intervention targets.…”
Section: Discussionmentioning
confidence: 99%
“…Renaming or reframing the meaning have been suggested as potential strategies to address negative perceptions of PC. [ 31 , 32 , 33 ]. Interestingly, adding to these known challenges, we found that professional role is a factor, with concerns about patients’ negative perceptions of PC perceived as an even greater barrier by nurses, allied healthcare professionals, and radiation therapists than physicians.…”
Section: Discussionmentioning
confidence: 99%
“…We employed semi-structured telephone interviews. We chose telephone interviews because they were suggested by patients who found comfort and convenience sharing their experiences over the phone (Ahmed et al, 2020). The interview guide was developed in collaboration with palliative care specialist clinician-researchers and three patient and family advisors on the team.…”
Section: Methodsmentioning
confidence: 99%
“…We compared these interviews to those conducted by our team with another cohort of patients living with advanced colorectal cancer receiving care prior to implementation of the early palliative care pathway (Ahmed et al, 2020). Demographic details of both interviews and the comparison of the experiences before and after implementation of the early palliative care pathway are summarized in Table 3.…”
Section: Comparison With Patient Experiences Prior To Palliative Care...mentioning
confidence: 99%
See 1 more Smart Citation